The Association between COVID-19 Infection and both rs34224237IL-6 and rs1800871 IL-10 Gene Polymorphisms - Salih, Abdulazeez (University of Thi-Qar Journal of Science, 2025)
Investigate the polymorphism of the IL-6 and IL-10 genes in COVID-19 patients was the goal of this study. Fifty COVID-19 patients and 50 samples as control used in this study on 7/12/2023. The results recorded that a significantly relation (P= 0.03) of rs34224237 (AAAAAAAAA SNP) was detected in the studied samples (COVID-19) and control, that variation of A nucleotide in position 22726806. While, the results of this study showed a high significantly relationship (P= 0.0007) of rs1800871 (A>G) in position 206773289. In conclusion, This study showed the polymorphism of IL-10 (rs1800871, A>G SNP) was a highly significantly associated with COVID-19 infection, which could be employed as a diagnostic marker for COVID-19 infections.